Strengthen the Judiciary's Independence in Europe! : -International Recommendations for an Independent Judicial Power-. - Albrecht, Peter-Alexis (BWV Berliner Wissenschafts-Verlag, 2010)
HauptbeschreibungThe Consultative Council of European Judges at the Council of Europe (CCJE) rightly characterized judicial autonomy, that is, the independence of impartiality of the third state power, as a "structured requirement of a state governed by the rule of law" (cf. position no. 8 from no. 10/2007 in the appendix). To do justice to the principle of the separation of powers as an accomplishment of the European Enlightenment, the autonomy of the third power must be subject to the same basic principles throughout Europe as the European Union draws closer together. Until this happens, it.